2016
DOI: 10.1016/j.jtho.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in Resected Invasive Mucinous Adenocarcinomas of the Lung: Related Factors and Comparison with Resected Nonmucinous Adenocarcinomas

Abstract: Patients with IMA demonstrate a DFS between that of patients with low-grade nonmucinous ADC and that of patients with intermediate-grade nonmucinous ADC and an OS similar to that of patients with intermediate-grade nonmucinous ADC. In IMA, tumor size and maximum standardized uptake value are the factors related to mitigating DFS and tumor size is the only predictor for reduced OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
78
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 29 publications
17
78
2
Order By: Relevance
“…When compared with 5 major nonmucinous adenocarcinoma subtypes, the DFS and OS curves of IMA were running between ACN/PAP and SOL/MIP subgroups. These results were consistent with our (Cai et al 2014) and other's (Lee et al 2016) previous similar studies. To distinguish the impact of mixed nonmucinous component on patients' prognosis, further analyses demonstrated the DFS and OS curves of pure mucinous were closely to lepidic adenocarcinoma, with a nearly 100 % 5-year disease free survival.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…When compared with 5 major nonmucinous adenocarcinoma subtypes, the DFS and OS curves of IMA were running between ACN/PAP and SOL/MIP subgroups. These results were consistent with our (Cai et al 2014) and other's (Lee et al 2016) previous similar studies. To distinguish the impact of mixed nonmucinous component on patients' prognosis, further analyses demonstrated the DFS and OS curves of pure mucinous were closely to lepidic adenocarcinoma, with a nearly 100 % 5-year disease free survival.…”
Section: Discussionsupporting
confidence: 94%
“…Clinically, IMA have a tendency for multicentric, multilobar involvement (Travis et al 2011). The prognosis of IMA remains controversial (Cai et al 2014;Eberhard et al 2005;Lee et al 2016;Warth et al 2012;Yanagawa et al 2013). Previous reports demonstrated that IMA have a correlation with poor prognosis (Yanagawa et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this negative value in terms of prognosis was not an independent factor by multivariate analysis. It is known that TTF1 expression is a favorable prognostic factor, and prognosis of the invasive mucinous tumors is inferior to that of low‐grade non‐mucinous tumors in lung adenocarcinoma . As VSIG1 expression in lung adenocarcinomas was confounded with a loss of TTF1 expression, invasive mucinous subtype, and advanced disease stage, the results of survival analyses should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 IMA is defined as adenocarcinoma that is characterized by a goblet or columnar cell morphology with abundant intracytoplasmic mucin. 2 Although the clinical, pathological, and genetic characteristics of IMA have been revealed in recent reports, [3][4][5][6][7][8][9][10][11][12][13] the prognosis and prognostic factors have not yet been clarified, due to its rare incidence as it accounts for only 5% of all lung adenocarcinomas. 2 In previous studies, IMA had distinct clinical, pathological, and genetic differences from non-mucinous adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%